A IMPLEMENTASI TERM FREQUENCY – INVERSE DOCUMENT FREQUENCY (TF-IDF) DAN VECTOR SPACE MODEL (VSM) UNTUK PENCARIAN BERITA BAHASA INDONESIA - Wiyanto W; Wowon Priatna; Jumi Saroh Hidayat (DPPM Universitas Pelita Bangsa, 2019)
A search engine that already exists and widely used today can be provide the result of information very much, so it takes time to sort through the information in need. The research with the title